A Tortonian onset for the Algerian margin inversion: Evidence from low‐temperature thermochronology. (17th December 2018) - Recanati, Alice; Missenard, Yves; Leprêtre, Rémi; Gautheron, Cécile; Barbarand, Jocelyn; Abbassene, Fatiha; Abdallah, Nachida; Ouabadi, Aziouz; Derder, Mohamed El Messaoud; Boukari, Claire; Pinna‐Jamme, Rosella; Haurine, Frédéric
Abstract: In North Africa, the Algerian margin is made of basement blocks that drifted away from the European margin, namely the Kabylia, and docked to the African continental crust in the Early Miocene. This young margin is now inverted, as dated Miocene (17 Ma) granites outcrop alongshore, evidencing kilometre‐scale exhumation since their emplacement. Age of inversion is actually unknown, although Pliocene is often considered in the offshore domain. To decipher the exhumation history of the margin between 17 and 5 Ma, we performed a coupled apatite fission track (AFT) and (U–Th–Sm)/He (AHe) study in the Cap Bougaroun Miocene granite. AFT dates range between 7 ± 1 and 10 ± 1 Ma, and mean AHe dates between 8 ± 2 and 10 ± 1 Ma. These data evidence rapid and multi‐kilometre exhumation during Tortonian times. This event cannot be related to slab break‐off but instead to the onset of margin inversion that has since developed as an in‐sequence north‐verging deforming prism.